2005
DOI: 10.1103/physrevd.71.129906
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Scaling of multitension cosmic superstring networks [Phys. Rev. DPRVDAQ0556-282171, 103508 (2005)]

Abstract: Brane inflation in superstring theory ends when branes collide, initiating the hot big bang.Cosmic superstrings are produced during the brane collision. The cosmic superstrings produced in a D3-brane-antibrane inflationary scenario have a spectrum: (p, q) bound states of p fundamental (F) strings and q D-strings, where p and q are coprime. By extending the velocity-dependent onescale network evolution equations for abelian Higgs cosmic strings to allow a spectrum of string tensions, we construct a coupled (inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
153
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(163 citation statements)
references
References 21 publications
(16 reference statements)
9
153
1
Order By: Relevance
“…By studying the asymptotic scaling properties of these networks in generic expanding universes we have confirmed two classes of solutions: one corresponds to the well-known linear scaling solution, while the other corresponds to the case where the curvature is concentrated in the wall junctions. Our results complement those for cosmic strings [18,19], though we emphasize that the way we model the network is slightly different and aims to model the properties that are more easily measurable in field theory numerical simulations.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…By studying the asymptotic scaling properties of these networks in generic expanding universes we have confirmed two classes of solutions: one corresponds to the well-known linear scaling solution, while the other corresponds to the case where the curvature is concentrated in the wall junctions. Our results complement those for cosmic strings [18,19], though we emphasize that the way we model the network is slightly different and aims to model the properties that are more easily measurable in field theory numerical simulations.…”
Section: Discussionsupporting
confidence: 64%
“…The purpose of this model is to describe the interaction between the different types of defects, in order to determine if this kind of networks can reach a scaling regime, as suggested in [18,19]. Additional motivation for working with three types of walls is also provided by [19], who find that in the case of cosmic strings the three lightest components dominate the dynamics, with the heavier ones being suppressed.…”
Section: Multiple Tensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, it has been shown that it is possible for non-intercommuting strings to reach a scaling solution [7]. Furthermore, a careful study of Type I strings reveals that in fact they do intercommute, except when the angle between the colliding strings is small [3,8].…”
mentioning
confidence: 99%